The Effectiveness of Guided Inquiry-Based Physics Instruction Integrating Real and Virtual Laboratories in Developing Students’ Science Process Skills - Zulfa Nifa Safitri; Abdul Salam; Qamariah Qamariah (Universitas Lambung Mangkurat, 2026)
The often-abstract nature of direct current electricity concepts necessitates a learning model focused not only on theoretical mastery but also on developing students' practical skills. The integration of real and virtual laboratories within a guided inquiry framework offers the potential to bridge the gap between theoretical concepts and their practical applications. Therefore, this study aims to examine the effectiveness of guided inquiry-based physics instruction integrated with real and virtual laboratories on direct current electricity in fostering students’ science process skills. The study employed a pre-experimental method with a one-group pretest–posttest design, involving a single class from a public senior high school in Banjarmasin. The research instruments consisted of a learning outcome test comprising five essay questions and an observation sheet for students’ science process skills. The analysis revealed an average N-gain score of 0.57, which falls into the moderate category. The highest proportion of learning objectives achieved was found in the indicator of understanding Kirchhoff’s First Law, with a score of 0.84. Furthermore, students’ science process skills showed improvement, with mean scores across three consecutive sessions of 3.39, 3.00, and 3.64. These findings indicate that guided inquiry-based instruction utilizing both real and virtual laboratories is effective in enhancing students’ learning outcomes while simultaneously fostering their science process skills. Thus, this approach has the potential to be implemented as an innovative strategy in physics instruction, particularly in the topic of direct current electricity.